When hip-hop meets CMC: digital discourse in Nigerian hip-hop. Issue 4 (3rd July 2020) - Onanuga, Paul Ayodele
ABSTRACT: Mobile telephony and the Internet have ensured that digitized communication is a routine in which everyone engages. Since music artistes use their songs as archival tools in documenting social events and changes, we consider, in this study, the (re)presentation of Computer Mediated Communication in Nigerian Hip-hop. To this end, six purposively selected songs by six Nigerian hip-hoppers are subjected to textual analysis. It is noted that the cross re-territorialization of CMC in Hip-hop was explicated thematically through depictions of internet crime, romance and the necessity to be successful regardless of prevailing challenges. Slangification using technology-based lexis was further identified as a means to code online criminal activities as well as sexual relations. The findings reinvigorate a post-digital popular culture phenomenon and reflect Nigerian Hip-Hop as a cultural signifier of the contemporary crisis of identity and prevailing post-colonial realities